2021
DOI: 10.1016/j.eclinm.2021.101026
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric BMI changes during COVID-19 pandemic: An electronic health record-based retrospective cohort study

Abstract: Background: Beginning March 2020, the COVID-19 pandemic has disrupted different aspects of life. The impact on children's rate of weight gain has not been analysed. Methods:In this retrospective cohort study, we used United States (US) Electronic Health Record (EHR) data from Optum® to calculate the age-and sex-adjusted change in BMI ( BMI adj ) in individual 6to-17-year-old children between two well child checks (WCCs). The mean of individual BMI adj during 2017-2020 was calculated by month. For September-Dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
85
5
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(115 citation statements)
references
References 21 publications
8
85
5
6
Order By: Relevance
“…Our findings are in line with several studies on COVID-19-related weight changes in adults [ 9 , 10 ] and children [ 31 – 34 ] and studies on weight gain in children associated with the economic crisis in 2007–2008 [ 17 , 18 , 35 ] or the great Fukushima earthquake 2011 [ 19 , 36 ]. Zheng et al showed that the initial increase of BMI and obesity prevalence persisted or even aggravated at least two years after the earthquake.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings are in line with several studies on COVID-19-related weight changes in adults [ 9 , 10 ] and children [ 31 – 34 ] and studies on weight gain in children associated with the economic crisis in 2007–2008 [ 17 , 18 , 35 ] or the great Fukushima earthquake 2011 [ 19 , 36 ]. Zheng et al showed that the initial increase of BMI and obesity prevalence persisted or even aggravated at least two years after the earthquake.…”
Section: Discussionsupporting
confidence: 92%
“…In line with our results, they found an excessive acceleration of BMI-SDS change in the younger children, with rates two times as high as before. Moreover, they also found children with overweight and obesity more severely affected than their normal weight peers [ 34 ]. In addition, several other studies reported a remarkable weight gain in children associated with COVID-related lockdown periods (Korea, n = 169, pediatric patients [ 38 ]; US, n = 29, elementary school children [ 39 ]; China, n = 445, children aged 7–12 years [ 40 ]; China, n = 10,082, students of high schools, colleges, and graduate schools aged >16 years [ 41 ]; Italy, n = 51, adolescents with obesity aged 10–18 [ 32 ]; Greece n = 397, children and adolescents aged 2–18 years [ 42 ]).…”
Section: Discussionmentioning
confidence: 99%
“…BMI for age was slightly higher in the 2020 COVID-19 context preschool group (16.4 ± 2.6 kg/m 2 ) compared to the 2019 group (15.8 ± 1.6 kg/m 2 ). This is consistent with reports worldwide that identify an increase in BMI as a result of COVID-19 in preschoolaged children [48][49][50], youth 6-12 years [51], and adults [52]. However, the increased BMI appears to conflict with the increased healthy eating CHEERS subscale, MVPA levels, and step count in the 2020 COVID-19 context preschoolers.…”
Section: Covid-19 and Preschooler's Bmisupporting
confidence: 90%
“…Previous research has shown the importance of active solicitation of information [68] and EMRs are now being used to help evaluate the effectiveness [69] and potential side effects [70,71] of COVID-19 vaccines. Similarly, EMR-based data has been utilized previously in studies looking at the effects of the COVID-19 pandemic as a stressor on people with bipolar disorder [72], the safety of the COVID-19 vaccine in pregnant women [73], the effect of COVID-19 on pregnancy outcomes [74], the effects of clinical characteristics on outcomes of COVID-19 patients [75][76][77], the factors that influence pharmacotherapy for tobacco dependence in the VA system [78], the effect of mental health disorders on COVID-19 mortality [79], COVID-19 vaccine adverse effects [68], and the effects of the COVID-19 pandemic on body mass index in children [80]. Thus, the present study builds upon a growing body of research examining similar effects of the COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%